O efeito na evoluç\~ao da produtividade do trabalho da indústria Brasileira devido a mudanças tecnológicas nas suas cadeias produtivas (1990-2009) - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper tries to mesure the labour productivity in the Brazylian industry from 1990 until 2009. We do note consider the sectors one by one only, but their supply chains and intersectorial relationships. Besides, we mesure the evolution of labour productivity caused exclusively by technological changes. Finally, we consider the dynamic relationships among all the sectors together that are mobilized by production of each final sector. So it is possible to know what intersectorial relationship (backward or forward the sector itself) has influence (and how) above labour productivity evolution of the supply chain. We conclude that Brazylian industry did not walked a percurse of productive degradation after 1999, or even of a generalized labour productivity fall.
Keywords: D20; 330; Brazylian industry; labour productivity; technology